Soyedina Ricker, 1952 (Plecoptera: Nemouridae) in the eastern Nearctic: review of species concepts, proposed morphology-based species groups, and description of a new species from North Carolina - Grubbs, Scott A.; Baumann, Richard W. (Zootaxa, 2019)
The eastern Nearctic species of the genus Soyedina Ricker, 1952 (Plecoptera: Nemouridae) are reviewed. Two morphology-based species groups are proposed based on epiproct characteristics. Soyedina sheldoni sp. nov. is described from the southern Appalachian Highland region of western North Carolina. A distribution map and a dichotomous key to all nine Nearctic species are provided.